Simplicity theory - Kim, Byunghan (Oxford logic guides, 2014)
This title is about simple first-order theories. In the mid-1990s the author established in his thesis the symmetry and transitivity of non-forking for simple theories and, type-amalgamation for Lascar strong types. Since then a great deal of research work on simplicity theory, the study of simple theories and structures has been produced. This book starts with the introduction of the fundamental notions of dividing and forking, and covers up to the hyperdefinable group configuration theorem for simple theories.